Safety of synchronous prophylactic ablation of the anterior saphenous vein in patients undergoing great saphenous vein thermal ablation- 6 months follow-up data of the SYNCHRONOUS study - Dietrich, Carmen; Hirsch, Tobias; Hartmann, Karsten; Mattausch, Thomas; Wenzel, Hans-Christian; Zollmann, Philipp; Veltman, Jürgen; Weiler, Thomas K; Lengfellner, Guido; Müller, Lars; Stücker, Markus; Pannier, Felizitas; et al. (Phlebology, 2024)
Background - The SYNCHRONOUS-study investigates simultaneous ASV-ablation with great saphenous vein (GSV) treatment in endovenous laser ablation (EVLA) for preventing varicose vein recurrence. This sub-study examines complication rates associated with prophylactic ASV-ablation. - Methods - Among 1173 patients with refluxing GSV, 604 underwent GSV-ablation only, and 569 received additional ASV-ablation. Complication rates were compared over 6 months. - Results - Approximately 80% of patients were complication-free with minor bruising and dysesthesia being most common complications. After 6 months, additional prophylactic ASV-ablation did not increase the rate of complications compared to GSV-only treatment. - Conclusion - The 6-months follow-up data suggests that prophylactic ASV-closure, alongside GSV-treatment, is safe, with similar complication rates to GSV-only EVLA.
Online veröffentlicht: 30. Mai 2024
Gesehen am 21.01.2025